Predictors of Difficult Intubation in Patients With Ankylosing Spondylitis: Do Disease Activity and Spinal Mobility Indices Matter? - Nilgun ÜSTÜN; Fatih TOK; Işıl DAVARCI; Erman YAĞIZ; Hayal GÜLER; Selim TURHANOĞLU; Ayşe TURHANOĞLU (Archives of Rheumatology, 2014)
Objectives: This study aims to determine the predictors of difficult intubation and their possible correlations with disease activity and spinal mobility indices in patients with ankylosing spondylitis. Patients and methods: Forty-five ankylosing spondylitis patients were included in the study. Disease activity was evaluated with the Bath Ankylosing Spondylitis Disease Activity Index and spinal mobility with Bath Ankylosing Spondylitis Metrology Index (BASMI). The predictors of difficult intubation were evaluated by using the modified Mallampati test, upper lip bite test, thyromental distance, sternomental distance, inter-incisor distance and neck extension. Results: There was no correlation between Bath Ankylosing Spondylitis Disease Activity Index and predictive test values (all p>0.05). There were significant correlations between BASMI with modified Mallampati test, sternomental distance, neck extension, and inter-incisor distance values (all p<0.05). The BASMI scores in patients with two or more predictors were significantly higher than BASMI scores in patients with none or one predictor (5.28±2.12 vs. 1.58±1.50; p<0.001). Among the patients with moderate to severe BASMI, the number of patients with two or more predictors was higher than in those patients with none or one predictor (p=0.001). Conclusion: Neck extension, inter-incisor distance, sternomental distance and modified Mallampati test are significant predictors for difficult intubation in patients with ankylosing spondylitis. These predictors were found to be correlated with spinal mobility index, but not with disease activity index. Clinicians should be aware of difficult intubation in ankylosing spondylitis patients with moderate to severe spinal mobility limitation.